Analysis of Factors Affecting BPJS Patients Choosing a Class of Care to VIP Room - Febrian Purwatiningrum (Journal for Quality in Public Health, 2019)
The increase of assurance participant, impact to increase inpatient at hospital. Some of participant choose to upgrade their treatman class, really if they don’t upgrade treatmen class they don’t need to pay more for their treatman. Purpose of this research are analysis factors that influence behaviour to upgrade class treatmen to VIP class at dr.Iskak hospital that include of perception, knowledge,income, and family support.This is a kuantitatif reseach with approch cross sectional. The population was all BPJS patient that treat at VIP dr. Iskak hospital Tulung Agung since 1st June until 31 of July 2018. Sample of research were some of BPJS patients that treated at VIP class dr.Iskak hospital Tulungagung = 182.The data collect by simple ramdom sampling. Independent variables are Perception, Income,Knowledge, Family Support. Dependent variable is Upgrade treatment class to VIP. Statistic analysis with logistic regression. Result of the research, all of independent variable are simultanetaneously influence BPJS patient choosing to upgrade treatmen class to VIP class at dr.Iskak hospital Tulungagung p value=0,008. In partial, perception p-value 0,956 ( >0,05 ), income p-value 0,001 ( <0,05 ), knowledge p-value 0,854 ( >0,05 ), family support p-value 0,021 (< 0,05).In this research, income and family support are influencing BPJS patient to upgrade treatmen class. But perception and knowledge are not influencing. And the dominan factor is income. Without good income, behaviour upgrade class treatmen not going to do